Extracellular enolase of Candida albicans is involved in colonization of mammalian intestinal epithelium - Silva, Richard C.; Padovan, Ana Carolina B.; Pimenta, Daniel C.; Ferreira, Renata C.; da Silva, Claudio V.; Briones, Marcelo R. S. (Frontiers in Cellular and Infection Microbiology, 2014)
Enolase is secreted by C. albicans and is present in its biofilms although its extracellular function is unknown. Here we show that extracellular enolase mediates the colonization of small intestine mucosa by C. albicans. Assays using intestinal mucosa disks show that C. albicans adhesion is inhibited, in a dose dependent mode, either by pretreatment of intestinal epithelium mucosa disks with recombinant C. albicans enolase (70% at 0.5 mg/ml enolase) or by pretreatment of C. albicans yeasts with anti-enolase antibodies (48% with 20 µg antiserum). Also using flow cytometry, immunoblots of conditioned media and confocal microscopy we demonstrate that enolase is present in biofilms and that the extracellular enolase is not an artifact due to cell lysis, but must represent functional secretion of a stable form. This is the first direct evidence that C. albicans extracellular enolase mediates colonization on its primary translocation site. Also, because enolase is encoded by a single locus in C. albicans, its dual role peptide, as glycolytic enzyme and extracellular peptide, is a remarkable example of gene sharing in fungi.